2002
DOI: 10.1590/s1516-635x2002000100004
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da Densidade de Criação e do Sexo Sobre o Empenamento, Incidência de Lesões na Carcaça e Qualidade da Carne de Peito de Frangos de Corte

Abstract: O experimento foi conduzido nas instalações experimentais da Faculdade de Medicina Veterinária e Zootecnia - UNESP, Campus de Botucatu, SP, Brasil, com o objetivo de avaliar o efeito da densidade de criação e do sexo sobre o empenamento, incidência de lesões na carcaça e a qualidade de carne de peito de frangos de corte. Foram utilizados 1950 pintos de corte sexados, da linhagem Ross, distribuídos em um delineamento inteiramente casualizado, com esquema fatorial com 3 densidades (10, 13 e 16 aves/m²) e dois se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 9 publications
3
22
0
8
Order By: Relevance
“…Graças et al (1990), affirms that a reduction in feed intake can be caused by increased in housing density, with less physical space, the birds have difficult access to feeders for these. However, according to the results of Garcia et al (2002) and Cruz et al (2013), increasing housing density can promote greater results of meat/m², therefore, an alternative to increase the productive and economic performance of poultry production. Moreover, to formulate an ideal diet, that is, to present maximum performance and economic results, it's necessary to deeply understand the nutritional poultry requirements (Trindade Neto et al, 2009), as proposed in this study, from the results that demonstrated the better nutritional energy-protein relations for ducks.…”
Section: Performance Carcass Traits and Economic Availability Of Musmentioning
confidence: 99%
“…Graças et al (1990), affirms that a reduction in feed intake can be caused by increased in housing density, with less physical space, the birds have difficult access to feeders for these. However, according to the results of Garcia et al (2002) and Cruz et al (2013), increasing housing density can promote greater results of meat/m², therefore, an alternative to increase the productive and economic performance of poultry production. Moreover, to formulate an ideal diet, that is, to present maximum performance and economic results, it's necessary to deeply understand the nutritional poultry requirements (Trindade Neto et al, 2009), as proposed in this study, from the results that demonstrated the better nutritional energy-protein relations for ducks.…”
Section: Performance Carcass Traits and Economic Availability Of Musmentioning
confidence: 99%
“…Feathering was evaluated according to the standard 0-10 score scale proposed by Garcia et al (2002).…”
Section: Evaluation Of Feathering Lesions Incidence and Litter Compamentioning
confidence: 99%
“…The types of lesions found and bird identification number were recorded in a specific spreadsheet. The presence of lesions was recorded as recommended by Garcia et al (2002).…”
Section: Birds Management and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…CV: Coeficiente de Variação. Garcia et al (2002), estudando a incidência de lesões em frangos de corte nas densidades de 10, 13 e 16 aves m -2 , no mesmo sistema de automatização, observaram as maiores médias para hematomas, calos de peito, cochim de plantar, arranhões e dermatite lombar nas maiores densidades.…”
Section: Resultsunclassified